Identifikasi Glikosida dan Evaluasi Fisik Formula Pemanis Rendah Kalori Tanaman Stevia (Stevia rebaudiana Bentoni) Pada Minuman Fungsional Bir Pletok - indahsari, dita dwi; Nasyanka, Anindi Lupita; Na'imah, Janatun (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2020)
Instant drinks, which are often consumed by the public, are mostly sweetened drinks that contain high calories and artificialsweeteners and can cause various diseases, such as obesity, cancer, diabetes and others. This can be controlled and prevented by consuminglow-calorie sweeteners. Stevia is a plant that has a sweetness of 300 times that of sucrose, so it can be used as a low-calorie sweetener, suchas in the functional drink Pletok beer. This study aims to identify glycosides and to evaluate the physical evaluation of the low-caloriesweetener formula for Stevia (Stevia rebaudiana B.) in the functional beverage of Bir Pletok. Physical evaluation and hedonism test werecarried out on 20 panelists and 1 expert panelist, then analyzed descriptively. In this study, several tests of instant preparations were carriedout, namely organoleptic test, pH test, specific gravity test, movable volume test and hedonism test on 20 panelists and 1 expert panelist. Theresults of the research that have been done show that the leaves of Stevia (Stevia rebaudiana B.) contain diterpenoid glycosides and based onall test preparations the best formula of the three formulas is Formula II. Keywords: Sweeteners, Stevia, Functional Drinks, Bir Pletok, Glycosides.